2013
DOI: 10.1186/1472-6882-13-103
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of genistein on radiation-induced intestinal injury in tumor bearing mice

Abstract: BackgroundRadiation therapy is the most widely used treatment for cancer, but it causes the side effect of mucositis due to intestinal damage. We examined the protective effect of genistein in tumor-bearing mice after abdominal irradiation by evaluation of apoptosis and intestinal morphological changes.MethodsMouse colon cancer CT26 cells were subcutaneously injected at the flank of BALB/c mice to generate tumors. The tumor-bearing mice were treated with abdominal radiation at 5 and 10 Gy, and with genistein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 37 publications
(59 reference statements)
2
34
0
Order By: Relevance
“…Kim et al (2012) indicated that they are very sensitive biodosimetric markers after irradiation process. Acute effects of irradiation on the intestinal mucosa may be attributed to inhibition of mitotic divisions in the Lieberkühn crypts, and the loss of proliferative functions results in drop in the development of the small intestine epithelium and reduces the small intestine permeability to gut bacteria and antigens, which may intensify mucosal inflammation and dysfunction or lead to bacteremia (Son et al, 2013). The current study showed that 6 Gy whole body gamma irradiation of male albino rats triggered oxidative stress indicated by a highly significant increase in the oxidant biomarkers (AOPP and MDA) and a highly significant decrease in antioxidant enzyme activity (CAT and GSH-Px).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2012) indicated that they are very sensitive biodosimetric markers after irradiation process. Acute effects of irradiation on the intestinal mucosa may be attributed to inhibition of mitotic divisions in the Lieberkühn crypts, and the loss of proliferative functions results in drop in the development of the small intestine epithelium and reduces the small intestine permeability to gut bacteria and antigens, which may intensify mucosal inflammation and dysfunction or lead to bacteremia (Son et al, 2013). The current study showed that 6 Gy whole body gamma irradiation of male albino rats triggered oxidative stress indicated by a highly significant increase in the oxidant biomarkers (AOPP and MDA) and a highly significant decrease in antioxidant enzyme activity (CAT and GSH-Px).…”
Section: Discussionmentioning
confidence: 99%
“…Different concentrations of GEN (1, 5, 10, 20 μM) were applied in the GEN treatment group 24 h prior to X ray irradiation, and were also present in the medium after irradiation. Cells were irradiated with different doses of X rays (6,8,12,16,20 Gy) (Varian 2100, C/D linear accelerator) at a dose rate of 300 cGy/min, and were harvested 24, 48 and 72 h after irradiation.…”
Section: Cell Cultures and Treatmentmentioning
confidence: 99%
“…Other data demonstrated that GEN also had radioprotective effects in nonhematopoietic tissues, including the lung, testis and intestine [17][18][19]. Son et al [20] found that GEN had a protective effect on intestinal damage induced by irradiation and inhibited tumor growth. Our previous studies indicated that soybean isoflavone treatment could significantly alleviate the liver oxidative stress and damage induced by 60 Co-gamma irradiation [21].…”
Section: Introductionmentioning
confidence: 96%
“…Further, quantitative real-time polymerase chain reaction (qRT-PCR) microarrays examination of cell cycle specific genes in bone marrow cells have shown that GN-treated mice expressed fewer DNA damage responsive and cell cycle checkpoint genes than untreated controls, thereby providing protection from acute myelotoxicity (Davis et al, 2008). The radioprotective ability of GN was further supported by some of the recent works showing prevention of irradiation-induced damage to hematopoietic system and intestinal damages Son et al, 2013), and rendering delay in tumour growth (Son et al, 2013).…”
Section: Genisteinmentioning
confidence: 70%